Health Self-Efficacy Among Populations with Multiple Chronic Conditions: the Value of Patient-Centered Communication. Issue 8 (August 2016) - Finney Rutten, Lila; Hesse, Bradford; St. Sauver, Jennifer; Wilson, Patrick; Chawla, Neetu; Hartigan, Danielle; Moser, Richard; Taplin, Stephen; Glasgow, Russell; Arora, Neeraj
Abstract Introduction Using cross-sectional survey data, we assessed the association between chronic illness burden and health-related self-efficacy, evaluating whether patient-centered communication is associated with self-efficacy and if that relationship varies by chronic illness burden. Methods Data were from the Health Information National Trends Survey, a cross-sectional survey of the US adult population collected in 2012–2013 (n  = 3630). Health-related self-efficacy was measured with the item: "Overall, how confident are you about your ability to take good care of your health?" and the prevalence of six chronic conditions and depression/anxiety was assessed. Patient-centered communication was measured as the frequency with which respondents perceived their healthcare providers allowed them to ask questions, gave attention to their emotions, involved them in decisions, made sure they understood how to take care of their health, helped them to deal with uncertainty, and if they felt they could rely on their healthcare providers to take care of their healthcare needs. Results Health-related self-efficacy was significantly lower among individuals with greater illness burden. In adjusted analysis, individuals who experienced more positive patient-centered communication reported higher levels of self-efficacy (β  = 0.26, P  < 0.0001); this association was strongest among those with greater illness burden. Conclusion Higher levels of self-efficacy were observed among patients reporting more positive patient-centered communication; the observed association was stronger among those with greater chronic illness burden.